Effect of controlled internal drug release insert on conception rate of repeat breeder cows - CHANDEL, ANSHUL; SINGH, MADHUMEET; KUMAR, PRAVESH; SHARMA, AKSHAY (The Indian Journal of Animal Sciences, 2022)
The present study was aimed at improving the conceptionrate in repeat breeder cows (N=43) suffering from functional form of infertility with the use of controlled internal drugrelease device (CIDR) pre- and post-insemination. Repeatbreeder cows were divided into two treatment, i.e. CIDR-I(n=12) and CIDR-II (n=13), and one control group (n=18).The overall conception rate in first and second treatmentgroup, i.e. 58.33 and 61.54%, respectively, were nonsignificantlyhigher as compared to control group (22.22%).In conclusion, CIDR protocols fared better in achievingconception in repeat breeder cows.